2004
DOI: 10.1103/physrevlett.93.207201
|View full text |Cite
|
Sign up to set email alerts
|

Directional Ordering of Fluctuations in a Two-Dimensional Compass Model

Abstract: In the Mott insulating phase of the transition metal oxides, the effective orbital-orbital interaction is directional both in the orbital space and in the real space. We discuss a classical realization of directional coupling in two dimensions. Despite extensive degeneracy of the ground state, the model exhibits partial orbital ordering in the form of directional ordering of fluctuations at low temperatures stabilized by an entropy gap. Transition to the disordered phase is shown to be in the Ising universalit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 16 publications
7
95
0
Order By: Relevance
“…So the Hamiltonian is only invariant if one simultaneously performs the same rotation in real space and in pseudo-spin space. For purely orbital models, this is known to have remarkable consequences [34,35,36,37]. For spin-orbital models, this implies that dimers with different orientations involve different orbital wave-functions, as can be clearly seen in phases C and C'.…”
Section: Discussionmentioning
confidence: 96%
“…So the Hamiltonian is only invariant if one simultaneously performs the same rotation in real space and in pseudo-spin space. For purely orbital models, this is known to have remarkable consequences [34,35,36,37]. For spin-orbital models, this implies that dimers with different orientations involve different orbital wave-functions, as can be clearly seen in phases C and C'.…”
Section: Discussionmentioning
confidence: 96%
“…In that respect, it is useful to emphasize that, as noticed in Refs. [8,9], the degeneracy is partly accidental and partly due to symmetry. Indeed, in addition to the lattice translational symmetries, this model has two types of discrete symmetries: (i) The Q i transformation which flips the z component of all the spins of the column r x = i, and the P j transformations which flip the x component of all spins of the line r z = j.…”
Section: Semi-classical Compass Modelmentioning
confidence: 99%
“…Nussinov et al have shown that an order by disorder mechanism is expected to lift the rotational degeneracy and to select states in which the spins point along the x or z axis, leading to a nematic ground state since lines or columns of spins are still free to flip. Using extensive Monte Carlo simulations, Mishra et al have shown that the two possible orientations along x or z lead to an effective Ising order parameter, and that the model undergoes a finite temperature phase transition of the Ising type [9].…”
Section: Introductionmentioning
confidence: 99%
“…The sign of J has no relevance since it can be transformed away on bipartite lattices. 11 With N = L d we denote the number of spins on a cubic lattice of linear extension L and dimension d. It should be emphasized that in contrast to the CM in three dimensions (3D) or the Kitaev model in two dimensions (2D), quantum MC investigations of the POM can easily be done also in 3D since there is no sign problem. Note that the Hamiltonian (2) is Z 2 symmetric under exchange of sub-lattices A and B and spin indices x and z.…”
Section: The Modelmentioning
confidence: 99%
“…2(c,d), as expected. 11 A quantity directly probing a crystalline state as in Fig. 2(b) is for example a plaquette structure factor defined by…”
Section: A Néel Orderingmentioning
confidence: 99%